Interaction with longan seed polyphenols affects the structure and digestion properties of maize starch. (15th March 2021) - He, Ting; Wang, Kai; Zhao, Lei; Chen, Yan; Zhou, Wanxia; Liu, Fangmei; Hu, Zhuoyan
Highlights: Interaction with LSPs leads to reduced apparent amylose content of maize starch. LSPs showed apparent inhibition effect on the digestion of maize starch. LSPs tend to have hydrophobic interactions with mainly amylose after cooking. LSPs might enter the hydrophobic cavity of amylose and form V-type inclusion complex. Abstract: This study investigated effects of longan seed polyphenols (LSPs) on the structure and digestion properties of starch, and discussed the interaction mechanism between starch and LSPs. The results showed cooking with 20 % LSPs did not change amylopectin chain length distribution of normal maize starch, however, the amylose content was reduced from 21.60 to 14.03 %. This suggests LSPs may interact with starch via non-covalent bond. Isothermal titration microcalorimetry and XRD results confirmed the existence of non-covalent interaction, and indicated that LSPs may enter the hydrophobic cavity of amylose, forming V-type inclusion complex. LSPs did not affect gelatinization temperatures of maize starch, whereas 20 % LSPs decreased the enthalpy change by about 26 %. The digestion results indicate significant inhibition effect of LSPs on the digestion of cooked starch, attributing to the interaction of LSPs with starch. These suggest potential applications of LSPs as functional ingredients in modulating postprandial glycemic response of starchy food.